Journal of Iberian Geology - Journal of Iberian Geology (Springer Nature, 2026)
The Journal of Iberian Geology will consider for publication original, high-quality papers (including research articles, reviews and brief communications) dealing with different aspects of Earth Sciences in Latin America and the Caribbean, as well as the Mediterranean region, including Geology, Paleontology, Geophysics and Geochemistry. The journal welcomes research papers with regional appeal, but these should present results of international interest. The Journal accepts collections of selected original papers on topics within these scopes, which will be published as edited monographic issues.
FI 0.71
Q2
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; América Latina y el Caribe